2019
DOI: 10.1172/jci.insight.130441
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling reveals multiple abnormalities of myocardial noradrenergic function in Lewy body diseases

Abstract: IntroductionThe movement disorder in Parkinson disease (PD) results from depletion of the catecholamine dopamine in the brain's nigrostriatal system (1). PD also entails profound deficiency of the closely related catecholamine norepinephrine (NE) in the heart (2). Other Lewy body diseases -pure autonomic failure (PAF) and dementia with Lewy bodies -also involve severely decreased myocardial NE contents (3).The cardiac sympathoneural lesion in these diseases probably is important clinically. Thus, neuroimaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 44 publications
(62 reference statements)
6
29
0
Order By: Relevance
“…20 Outside the brain, in PD there is very prominent loss of NE in the left ventricular myocardium. [21][22][23] The extent of decrease in PD-90 to 99%-is similar to that of putamen dopamine. Several in vivo neuroimaging studies have indicated that in PD noradrenergic deficiency is cardioselective [24][25][26][27] ; however, postmor-tem NE tissue contents in extracardiac regions in PD have not yet been reported.…”
Section: Catecholamine Depletion In Neurodegenerative Diseasesmentioning
confidence: 69%
See 4 more Smart Citations
“…20 Outside the brain, in PD there is very prominent loss of NE in the left ventricular myocardium. [21][22][23] The extent of decrease in PD-90 to 99%-is similar to that of putamen dopamine. Several in vivo neuroimaging studies have indicated that in PD noradrenergic deficiency is cardioselective [24][25][26][27] ; however, postmor-tem NE tissue contents in extracardiac regions in PD have not yet been reported.…”
Section: Catecholamine Depletion In Neurodegenerative Diseasesmentioning
confidence: 69%
“…We have introduced the term "sick-but-not-dead" to refer to the occurrence of functional abnormalities in extant residual catecholaminergic neurons in diseases involving catecholaminergic neurodegeneration. 23 The following discussion describes examples of the sick-but-not-dead phenomenon in catecholaminergic neurons in the brain or heart in Lewy body diseases.…”
Section: Catecholamine Depletion In Neurodegenerative Diseasesmentioning
confidence: 99%
See 3 more Smart Citations